The Prevalence of Tooth Wear among a Group of Yemeni Adults. - Safa Al-hammadi; Mohammed Dubais; Ahmed Madfa (Universidad de Concepción., 2019)
This study aimed at investigating tooth wear prevalence and determining the associated factors among a group of Yemeni adults. It is a preliminary cross-sectional and analytical investigation conducted on 600 participants aged 20-50 years. The participants were purposively selected from two main cities (Sana'a and Aden) with an equal sample size and divided equally by gender. For administering a questionnaire, interviews were conducted with all participants before clinically examining them. Using the Tooth Wear Index (TWI), tooth wear was assessed. Data were analyzed using the chi-square test to identify the relationship between tooth wear and associated factors., Tooth wear was prevalent among 78.67% of the participants; of which 64.83% were in anterior teeth, 63.83% in posterior teeth, 74% in maxillary teeth, and approximately 74.5% in mandibular teeth. It also was 100% prevalent in the 31-40 and 41-50 age groups, while it was 67.2% in the 20-30 age group. This showed that tooth wear prevalence was significantly higher in the two oldest groups than in the youngest group (p<0.001). Moreover, khat chewing, location, highly frequent consumption of foods and high frequency of acidic drinks consumption were critical indicators of tooth wear. Besides, a low education level, smoking and a low socio-economic status were associated with tooth wear. Finally, the study revealed that tooth wear is highly prevalent among adults in two Yemeni cities, and socio-behavioral risk indicators such as khat chewing and cigarette smoking have a significantly association with tooth wear.